THE RELATIONSHIP BETWEEN 21ST CENTURY SKILLS AND STUDENT LEARNING OUTCOMES THROUGH THE APPLICATION OF PROBLEM BASED LEARNING MODELS IN CLASS X ENVIRONMENTAL CHANGE MATERIALS AT SMA NEGERI 5 MEDAN T.P 2023/2024 - Suriani, Cicik; Fadillah, Yulia Rahmah; Kairani, Anita (Universitas Negeri Medan, 2025)
This study aims to find out 21st century skills and student learning outcomes, determine the relationship between 21st century skills and student learning outcomes, and its contribution through the application of problem based learning models on environmental change materials. The population in this study is all class X students at SMA Negeri 5 Medan. The sample in this study is students in grades X-4 and X-7 totaling 71 students determined using random sampling techniques. This study uses a quantitative descriptive research method. The research instruments used are in the form of observation sheets, objective tests, and documentation. Data analysis consists of normality, linearity, correlation, hypothesis, and determination tests. The results of the study show that: 1) the 21st century skills of grade X students of SMA Negeri 5 get an average score of 2.65 included in the